Arabidopsis Spliceosome Factor SmD3 Modulates Immunity to Pseudomonas syringae Infection - Golisz, Anna; Krzyszton, Michal; Stepien, Monika; Dolata, Jakub; Piotrowska, Justyna; Szweykowska-Kulinska, Zofia; Jarmolowski, Artur; Kufel, Joanna (Frontiers in Plant Science, 2021)
SmD3 is a core component of the small nuclear ribonucleoprotein (snRNP) that is essential for pre-mRNA splicing. The role of Arabidopsis SmD3 in plant immunity was assessed by testing sensitivity of smd3a and smd3b mutants to Pseudomonas syringae pv. tomato (Pst) DC3000 infection and its pathogenesis effectors flagellin (flg22), EF-Tu (elf18) and coronatine (COR). Both smd3 mutants exhibited enhanced susceptibility to Pst accompanied by marked changes in the expression of key pathogenesis markers. mRNA levels of major biotic stress response factors were also altered upon treatment with Pseudomonas effectors. Our genome-wide transcriptome analysis of the smd3b-1 mutant infected with Pst, verified by northern and RT-qPCR, showed that lack of SmD3-b protein deregulates defense against Pst infection at the transcriptional and posttranscriptional levels including defects in splicing and an altered pattern of alternative splicing. Importantly, we show that SmD3-b dysfunction impairs mainly stomatal immunity as a result of defects in stomatal development. We propose that this malfunction of the stomata is the primary cause of an altered mutant response to the pathogen. Other changes in the smd3b-1 mutant involved enhanced elf18- and flg22-induced callose deposition, reduction of flg22-triggered production of early ROS and boost of secondary ROS caused by Pst infection. Together, our data indicate that SmD3 contributes to the plant immune response possibly via regulation of mRNA splicing of key pathogenesis factors.